A theoretical and experimental investigation of the heat transfer during film condensation of saturated and superheated Freon 12 and Freon 114 - Van der Walt, J.(Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- Universiteit van Stellenbosch, 1970.